Titanium mesh cages (TMC) in spine surgery - Grob, Dieter (Springer-Verlag, 2004)
The introduction of the titanium mesh cage (TMC) in spinal surgery has opened up a variety of applications that are realizable as a result of the versatility of the implant. Differing applications of TMCs in the whole spine are described in a series of 150 patients. Replacement and reinforcement of the anterior column represent the classic use of cylindrical TMCs. The TMC as a multisegmental concave support in kyphotic deformities and as a posterior interlaminar spacer or lamina replacement after wide laminectomy are additional applications. Implant subsidence, pseudarthrosis and implant loosening are the complications typically encountered with use of TMCs. The versatility of the implant permits its use in unusual surgical situations.